Prognostic and Clinicopathological Significance of SATB1 in Colorectal Cancer: A Meta-Analysis - Zhao, Jun; Tuo, Yajun; Luo, Wei; He, Shaojun; Chen, Yifei (Frontiers in Physiology, 2018)
Background: A large number of studies have reported the aberrant expression of special AT-rich sequence binding protein 1 (SATB1) in colorectal cancer (CRC). However, the role of SATB1 in CRC is still controversial. Therefore, we performed this meta-analysis to elucidate the prognostic and clinical value of SATB1 in CRC patients. Methods: We searched Web of Science, EMBASE and PubMed entirely in January 2018 to identify related articles. Pooled Hazard ratio (HR) was adopted to evaluate the prognostic value of SATB1 in CRC and odd ratio (OR) was used to assess the clinicopathological significance of SATB1 in CRC. Results: Ten eligible studies containing 7 on prognosis and 9 on clinicopathological characteristics were finally included in the present meta-analysis. Results revealed that patients with high expression of SATB1 tended to have shorter overall survival (OS) (pooled HR: 1.64, 95% CI: 1.04-2.57). Besides, we also discovered that the expression of SATB1 was associated with tumor differentiation (OR=1.88, 95 % CI=1.06-3.34), distant metastasis (OR=1.43, 95% CI=1.11-1.85) and lymph node metastasis (OR=1.50, 95% CI=1.03-2.19). Conclusion: Broadly speaking, our meta-analysis demonstrated that high expression level of SATB1 was related to poor prognosis in CRC patients.